1992
DOI: 10.1203/00006450-199204000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Adverse Effects of Valproic Acid on Ketogenesis and Liver Coenzyme A Metabolism by Cotreatment with Pantothenate and Carnitine in Developing Mice: Possible Clinical Significance

Abstract: ABSTRACT. Very young children with organic brain damage, intractable seizures, and developmental retardation are at particular risk of developing fatal hepatic dysfunction coincident with valproate therapy, especially if the children are also receiving other anticonvulsant drugs. The mechanism of valproate-associated hepatic failure in these children is unclear. There are two major theories of etiology. The first concerns the manyfold consequences of depletion of CoA due to sequestration into poorly metabolize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…There is sufficient information in the literature that SVP is metabolized to unsaturated toxic products in the body [33,34,35]. These studies have shown that metabolites formed by omega oxidation pathway, 2-n-propyl-4-pentenoic acid and other delta dehydrogenation products may cause hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…There is sufficient information in the literature that SVP is metabolized to unsaturated toxic products in the body [33,34,35]. These studies have shown that metabolites formed by omega oxidation pathway, 2-n-propyl-4-pentenoic acid and other delta dehydrogenation products may cause hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In acute acetaminophen toxicity, CoASH levels decrease simultaneously with decreasing HMGCS2 enzymatic activity (51,52). Potentially fatal valproic acid therapy-induced hepatic dysfunction, which is associated with impaired β-oxidation of fatty acids and ketogenesis due to sequestration of CoASH into poorly metabolized valproyl CoA, can be prevented by administration of CoASH precursors (53,54). In rodents, hepatic CoASH concentrations decrease in response to an HFD (55), while the concentration of pantothenic acid actually increases (56), suggesting that hepatic CoASH homeostasis is dysregulated in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant administration of L-carnitine and pantothenate was reported to overcome the feedback inhibition of PANK (13, 49). This success might reflect the fact that L-carnitine can accept acyl groups from acyl-CoA, thereby importing acyl groups into mitochondria to facilitate fatty acid β-oxidation and liberating CoA (50).…”
Section: Discussionmentioning
confidence: 99%